2019
DOI: 10.1371/journal.pntd.0007162
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of infection with dengue and Zika viruses in horses on French Pacific Islands

Abstract: New Caledonia and French Polynesia are areas in which arboviruses circulate extensively. A large serological survey among horses from New Caledonia and French Polynesia was carried out to investigate the seroprevalence of flaviviruses in the horse population. Here, 293 equine sera samples were screened for flaviviruses using a competitive enzyme-linked immunosorbent assay (cELISA). The positive sera were then confirmed using a flavivirus-specific microsphere immunoassay (MIA) and seroneutralization tests. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…When enough volume was available, bird serum samples were tested first using a commercial ID Screen West Nile Competition Multi-species ELISA kit, IDvet, Montpellier, France. Assays were performed according to the method described in Beck et al [50], and interpreted according to manufacturer's instructions. This ELISA test uses plates pre-coated with the envelope (E) protein of WNV and measures the competition between antibodies present in the animal serum tested and a monoclonal anti-WNV E antibody conjugated to horseradish peroxidase (HRP).…”
Section: Laboratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…When enough volume was available, bird serum samples were tested first using a commercial ID Screen West Nile Competition Multi-species ELISA kit, IDvet, Montpellier, France. Assays were performed according to the method described in Beck et al [50], and interpreted according to manufacturer's instructions. This ELISA test uses plates pre-coated with the envelope (E) protein of WNV and measures the competition between antibodies present in the animal serum tested and a monoclonal anti-WNV E antibody conjugated to horseradish peroxidase (HRP).…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Samples with % S/NC > 50% were considered negative. All positive samples by ELISA and all sera with insufficient volume and that could not be tested by ELISA were analyzed by microneutralization tests (MNT) on Vero NK cells, with the WNV lineage 1 IS-98-ST1 and USUV 206795/Italy 2012 strains (kindly provided by Philippe Desprès, IPP and D. Lelli, IZSLER respectively) following the protocol described in Beck et al [50]. Sera of birds was heat-inactivated at 56 • C for 30 min, then serially diluted (dilution factor of 2, 1/5 to 1/320) and mixed with a volume of 50 µL of Dulbecco's Modified Eagle's medium (DMEM), containing 100 tissue culture infectious dose 50 of WNV strain IS-89-ST1, or USUV strain 206795.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Serological diagnosis is especially challenging in regions with flavivirus cocirculation. In Brazil, epidemiological studies have demonstrated the presence of other flaviviruses of public health importance in the equine population, such as dengue virus (DENV), Zika virus (ZIKV), Mayaro virus (MAYV), Saint Louis Encephalitis Virus (SLEV), Ilhéus virus (ILHV), Iguape virus (IGUV), Rocio virus (ROCV) and Cacipacore virus (CACV) (Castro-Jorge et al, 2019;Beck et al, 2019). Since horses can be infected and seroconvert against these arboviruses of human importance, they serve as sentinels for these viruses as well.…”
Section: Important Topics To Consider In Brazilmentioning
confidence: 99%
“…However, the CDC does not specify which DENV serotype or whether multiple serotypes should be used [47]. A cursory examination into recent ZIKV serological studies shows that many laboratories employ a single strain of DENV for neutralization assays [48][49][50]. This could also lead to misdiagnosis of ZIKV since data throughout this manuscript have shown that neutralization of DENV by mAbs and subject sera is serotype specific.…”
Section: Discussionmentioning
confidence: 99%